Macro element for pile-head cyclic lateral loading, Special Topics in Earthquake Geotechnical Engineering, Geotechnical - Pender, M.J.; Wotherspoon, L.; Sa’don, N.M; Orense, R.P (SpringerLink, 2012)
Interaction between laterally loaded piles and the surrounding soil is a complex phenomenon, particularly when nonlinear soil behaviour is involved; so complex that usually design calculations rely on computer software based on discrete spring formulations using empirically derived nonlinear p-y relationships. This chapter explores a macro element, Davies and Budhu (1986), as an alternative which uses relatively simple formulae that are available for evaluating the lateral stiffness of long elastic piles embedded in elastic soil and an extension to handle nonlinear soil-pile interaction. The predictions of these equations are confirmed using the three dimensional finite element software OpenSeesPL, Lu et al. (2010), as well as data from field lateral load testing on driven piles in a stiff residual soil at a North Auckland site. Furthermore, in this chapter an extension of the macro element to cyclic loading is presented and this is shown to model well the field data and also the predictions of OpenSeesPL. The pile head macro element method is not completely general as it applies only to a homogeneous soil profile, but, since we deal with long piles, the soil homogeneity needs to extend only over the pile shaft active length. Measured lateral load response of the piles at the Auckland site indicates that it is necessary to distinguish the “operational” modulus of the soil from the small strain modulus; the field data indicates a value of about one third to one quarter of the small strain value.